Structural and magnetic properties of Ni1-xZnxFe2O4 synthesized through the sol-gel method - Guan, B.H. (American Institute of Physics Inc., 2016)
Modification of crystal structure by means of substitution would result in the modification of the overall physical properties of crystallite materials especially in ferrites. This study aims to investigate the effect of non-magnetic Zn substitution in spinel NiFe2O4 and its direct effect towards its microstructural and magnetic properties. Magnetic nanoparticles of Nickel-Zinc ferrite with the chemical formula, Ni1-xZnxFe2O4 (x=0.00, 0.25, 0.50, 0.75) were synthesized through the sol-gel route. Phase formation and structural properties of the synthesized ferrite were identified through X-ray diffraction (XRD) analysis and transmission electron microscopy (TEM). Magnetic properties such as the magnetic saturation, coercivity and remanence were measured by a vibrating sample magnetometer (VSM). XRD measurements reveals successful synthesis of single-phased Nickel ferrite and Nickel - Zinc ferrite. Both crystallite and grain size shows fluctuation with increasing Zn content. The ferrites were found to be ferrimagnetic in nature and show differing values with different x values. Â© 2016 Author(s).